Analisis Profitabilitas dan Solvabilitas Terhadap Return Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sherlly, Sherlly; Tipa, Handra (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to find out the impact of profitability and solvency on stock returns. Data used in this research is a literature study and documentation. The literature study in this research is obtained from journals and previous research results, while the documentation used in this study is obtained from financial reports published on the Indonesia Stock Exchange. The population in this study is a food & beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange with an observation period of 5 (five) years, from 2015 to 2019, 30 (thirty) companies are included in the population and by using the purposive sampling method. From the 30 (thirty) companies that fullfill the criteria to be sampled are 10 (ten) companies. The entire total sample data are 50. However, there are some data that are considered to be quite extreme, which results in data not being normally distributed, The total sample data after outliner testing was 47 sample data. The conclusion of this study indicared that partially profitability has a significant effect on stock returns, solvency has no significant effect on stock returns and simultaneously profitability and solvency have a significant effect on stock returns.